Development of vapour-grown carbon nano-fibre-reinforced aluminium matrix composites by low-pressure infiltration process. (November 2015) - Xu, Z. F.; Choi, Y. B.; Lee, M. H.; Zhao, Y. C.; Sugio, K.; Matsugi, K.; Sasaki, G.
Abstract : This study was aimed for development of vapour-grown carbon nano-fibre(VGCNF)-reinforced aluminium matrix composites by the low-pressure infiltration process. First, VGCNF and Al powder (VGCNF + Alp) preforms for low-pressure infiltration were fabricated by spark sintering process at pressures of 5, 10, 20 and 40 MPa, respectively. Porosity of the preforms fabricated at pressures of 5 and 10 MPa was 44·89 and 40·87%, respectively. However, porosity of the preforms fabricated by spark sintering at pressures of 20 and 40 MPa was approximately 20%. Therefore, VGCNF + Alp /Al composites with the preform sintered at pressures of 5 and 10 MPa were fabricated by the low-pressure infiltration process under an applied pressure of 0·4 MPa, and the relative density was 81·4 and 76·0%, respectively. Moreover, the microstructure, porosity and electrical conductivity of the VGCNF + Alp /Al composites were estimated. Their electrical conductivities reduced with increasing porosity of VGCNF + Alp /Al composites.